PENINGKATAN PRESTASI BELAJAR SISWA DALAM MENGARANG MELALUI PEMBELAJARAN TERBIMBING - Utami, Naning (Universitas Negeri Surabaya, 2017)
The writing lesson is actually very important given to the students to practice using the language actively. Our school in general is rather ignorant of writing lessons. The theoretical test material can lead to the motivation of the language teacher to teach the composing material only to be able to answer the exam questions, while the skill aspect is ignored. In addition to the above matters, it is assumed that some teachers who consider the authoring assignment given to the student are too burdensome or the task is too much for the student, so he feels sorry for the heavy burden to his students. Based on the above explanation, the researcher would like to try to do research with the title